Internal Investigations for Law Enforcement - Kroll, Rainer (Cham : Springer International Publishing : Imprint: Springer, 2023)
This concise volume provides a methodology for conducting investigations into allegations against law-enforcement officers. It takes into account the history of police culture, misconduct, and internal affairs investigations. Identifying three types of cases - administrative and rules violations, misconduct allegations, and crimes and corruption - this brief provides steps for the initial investigation, evidence retrieval, review of the investigation, and further considerations. Appropriate for students of criminal justice and law enforcement officers and researchers, this unique volume is a practical overview of common issues in and approaches to police misconduct. Provides a concise methodology for conducting investigations into law enforcement, outlining steps to take after receiving an allegation against an officer; Discusses various types of allegations, and the appropriate actions for pursuing each investigation; Examines the theory and history behind police culture and deviance, and behind internal affairs investigations.
1. Introduction -- 2. Underlying theory -- 3. History and justification -- 4. Types of cases -- 5. Types of allegations -- 6. Initial investigations -- 7. Typical investigative steps -- 8. Case closing dispositions -- 9. Case closing report -- 10. Proactive investigations -- 11. Liability.
Keywords: Criminology; Crime Control and Security